Weed Management In Groundnut (Arachis hypogaea L.) At Nawalpur Conditions In Sarlahi, Central Terai, Nepal (Agronomy Journal of Nepal, 2021)
Groundnut is one of the important summer oilseed crops of Nepal. The area under this crop has decreased considerably in the recent decade due to its high cost of cultivation for weeding and increased labor charge. Crop compete with the repeated flush of diverse weed throughout the growing season which causes substantial yield loss up to 50 -70 %. So, to find out an effective treatment for weed management, an experiment was conducted during 2017 and 2018 with nine treatments laid out in randomized complete block design (RCBD) in three replications. Treatments were constituted by four herbicides, two pre[1]emergence (pendimethalin and metribuzin) and two post emergences (quizalofop and propaquizafop). Pre emergence herbicide was followed by (fb) by hand weeding (HW) in one treatment and by the post emergence herbicides in another treatment. Cover mulch treatment with groundnut pods shell @ 3.0 t/ha was used. Farmer’s practice treatment consists of one hand weeding and one intercultural operation while no weeded plot was kept as control treatment. Data on weed dynamics, yield attributes and seed yield were varied among the treatments. Pre emergence herbicide supplemented by one hand weeding proved highly effective in controlling weeds. Pendimethalin @ 1.0 kg a.i/ha fb one HW showed superior performance in yield attributes, a high percentage (83.0%) of weed control efficiency (WCE), highest grain yield (2005 kg/ha), high benefits (NRs 222450) and BC ratio 2.84 among the treatments. The treatment metribuzin @ 0.5 kg a.i/ha fb one HW was also found as second best treatment with 74.4 % of WCE, yield (1882 kg/ha), benefits of Rs 205060 and BC ratio 2.65.